Child development - Santrock, John W. (McGraw-Hill, 2007)
John Santrock’s Child Development is widely considered the most accurate and up-to-date, topically-organized text in the field. Used by hundreds of thousands of students over ten editions, its learning-goals-driven learning system provides a clearer understanding of the content. The fully revised eleventh edition reinforces the highly contemporary tone and focus by featuring hundreds of new citations, including material from chapters from the sixth edition of the Handbook of Child Psychology .